(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Introduction: Monitoring and evaluation (M&E) practices play a crucial role in shaping the efficiency and effectiveness of healthcare systems. This study compares the understanding and implementation of M&E in two prominent Nigerian healthcare institutions, Lagos University Teaching Hospital (LUTH) and Mushin General Hospital (MGH). With an increasing emphasis on data-driven decision-making in healthcare, evaluating the impact of M&E practices is essential for improving patient outcomes and healthcare service quality. Objective: The study aims to assess the awareness, knowledge, and implementation of M&E practices among healthcare professionals in LUTH and MGH. Additionally, it explores the impact of M&E on patient records management and the efficiency of health information managers in both institutions. Methods of Analysis: A comparative research design was employed, involving a total of 150 participants from the Health Information Management departments of LUTH and MGH. Structured questionnaires were administered, and the data were analyzed using descriptive statistics, chi-square tests, and comparative figures to highlight significant differences. Results: The study reveals substantial awareness levels in both hospitals: 93.3% in LUTH and 94% in MGH. Chi-square tests show significant associations between M&E practices and the efficiency of health information managers: LUTH (p=0.04) and MGH (p=0.02). Furthermore, 69.6% of LUTH respondents and 75.0% of MGH respondents agreed that M&E enhanced healthcare services. Conclusion: The study underscores the pivotal role of M&E practices in healthcare management. Both hospitals exhibit a profound understanding of M&E, demonstrating its positive influence on healthcare services and patient record management. Recommendation: Healthcare institutions should conduct regular training sessions to enhance professionals’ M&E knowledge and skills. Implementation of integrated M&E systems across departments is crucial, and continuous evaluations are necessary to adapt to evolving healthcare needs and technological advancements.